从《英译离骚》看林文庆的翻译动机及手段 = On Lim Boon Keng's translation motive and approach : using "The Li Sao" as an example - 洪亿隽 Hong, Yijun (2013)
林文庆是著名的新加坡华人学者、政治家、教育家。但许多人却忽略了他在翻译方面的成就。林文庆精通双语，在文化意识上徘徊于东西方及中国新旧文化四者之间。他受过良好的英式教育，但却更钟爱中华文化，尤其对儒学深感兴趣。然而，林文庆一生坎坷。不管是在早期改革海峡华人的生活、或是后来在厦门大学任职校长，他的思想总与时代的潮流发生矛盾与冲撞。这时，林文庆“发现”了屈原，一位让他心灵上感应到惺惺相惜的战国时期的爱国诗人。于是，他投入了大量的心血研究并翻译了屈原的旷世之作《离骚》，连同其他相关的研究性内容和文章集成《英译离骚》，于1929年在上海出版。本文将以《英译离骚》为考察对象，探讨林文庆的翻译动机及手段。笔者试图将他翻译时期的历史背景及他本身的思想特征为基础，从文化意涵、教育意图及政治意义这三个层面去分析他译著《英译离骚》的目的，并以此来讨论《英译离骚》的出版。此外，笔者也会尝试分析《英译离骚》的翻译手段，谈谈林文庆使用异化翻译的原因及它存在的局限性。 Lim Boon Keng is a well-known Singaporean scholar, educator and politician. However, as people focus on his contributions in education and politics, many have neglected his achievements in the field of translation. Lim was bilingual and his ideologies mainly revolved between the Western, Asian, tradition and contemporary cultures. Though being well educated in English, Lim was fascinated by Chinese culture, and was particularly interested in Confucianism. Lim’s life had its ups and downs as his ideologies tend to be in conflict with then societal norms and beliefs. These deviations were evident when he promoted social reforms to improve the livelihood of Straits Chinese in Singapore, and when he served as the president of Xiamen University (then known as University of Amoy). It was then when Lim knew about Ch’u Yuan, a Chinese poet and politician who lived during the Warring States period of Ancient China, whom Lim’s heart felt close to. Hence, Lim devoted much of his efforts in researching and translating Ch’u Yuan’s masterpiece “The Li Sao”. Together with his other related research works, Lim published a translated piece of “The Li Sao” in Shanghai in 1929. This paper aims to study on Lim’s motives and approaches to translation, using “The Li Sao” as an example. The researcher uses characteristics of Lim’s ideology, as well as then historical background as basis of this research. Using a three-prong approach to analysis Lim’s motive of translating “The Li Sao”, and its publication in Shanghai, from cultural, educational and political perspectives. This study also attempt to analysis and understand Lim’s approaches to translating “The Li Sao”, and discuss reasons behind Lim’s use of “Foreignizing Translation” and its limitations.